indonesia Efforts of Islamic Religious Educational Institutions in the Era of Globalization - Al-Atsari, Abdul Rohman; Achadi, Muh. Wasith (Journal of Education Research, 2024)
This study aims to analyze the role and efforts of Islamic religious education institutions in facing the challenges of globalization. Globalization has a significant impact on the world of education, including Islamic education, by presenting opportunities to expand access to information and innovation, as well as challenges in maintaining Islamic values amid global cultural changes. The research method is a descriptive qualitative approach, collecting data through interviews and literature studies. The results showed that Islamic religious education institutions need to implement strategies that include the formation of self-awareness, integration of Islamic values with general knowledge, and applying adaptive learning methods. This effort is expected to form a generation that is not only intellectually competent but also has a strong personality in facing the negative impact of globalization.